Analisis Penerapan Bauran Pemasaran 4P (Product, Price, Place, Promotion) Terhadap Strategi Pemasaran Pada Kerajinan Rotan (Studi Kasus: UMKM Teq Production) - Erika Dwi Rahmawati; Diva Fitriyatin Nufus; Mohamad Bastomi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Rattan furniture is one of the superior craft products in Malang City, especially in the Balearjosari Village area, Blimbing District. UMKM Teq Production does not have an offline kiosk, which results in prices that cannot be set for each product sale. Even though crafts and furniture from UMKM Teq Production are in great demand abroad, they have to establish cooperative relationships with first-hand parties because they do not yet have an export trade business license. This problem can influence marketing strategies by implementing the 4Ps (Product, Price, Place, Promotion). The purpose of this article is to determine the influence of the 4P marketing mix (Product, Price, Place, Promotion) on Teq Production MSMEs which have been able to compete for 20 years now in the current competition. very tight. This research uses qualitative research methods with the type of library research when analyzing data in the field. Based on the results obtained by the author from interviewing sources, it can be concluded that the marketing mix with the 4P concept focuses on marketing success in the field of production of goods. All forms and types of marketing strategies carried out by a businessman to increase customer response and interest in the products being marketed. MSME owners need to pay attention to the 4P marketing mix in their marketing strategy for rattan crafts, apart from that, carrying out innovations regularly can improve product quality and even compete in the market and be able to export second hand.